Functional Improvement Trajectories After Surgery (FIT After Surgery) study: protocol for a multicentre prospective cohort study to evaluate significant new disability after major surgery in older adults. Issue 6 (22nd June 2022) - Wijeysundera, Duminda N; Alibhai, Shabbir M H; Ladha, Karim S; Puts, Martine T E; Chesney, Tyler R; Daza, Julian F; Ehtesham, Sahar; Hladkowicz, Emily; Lebovic, Gerald; Mazer, C David; van Vlymen, Janet M; Wei, Alice C; et al.
Abstract : Introduction: Older adults prioritise surviving surgery, but also preservation of their functional status and quality of life. Current approaches to measure postoperative recovery, which focus on death, complications and length of hospitalisation, may miss key relevant domains. We propose that postoperative disability is an important patient-centred outcome to measure intermediate-to-long recovery after major surgery in older adults. Methods and analysis: The Functional Improvement Trajectories After Surgery (FIT After Surgery) study is a multicentre cohort study of 2000 older adults (≥65 years) having major non-cardiac surgery. Its objectives are to characterise the incidence, trajectories, risk factors and impact of new significant disability after non-cardiac surgery. Disability is assessed using WHO Disability Assessment Schedule (WHODAS) 2.0 instrument and participants' level-of-care needs. Disability assessments occur before surgery, and at 1, 3, 6, 9 and 12 months after surgery. The primary outcome is significantly worse WHODAS score or death at 6 months after surgery. Secondary outcomes are (1) significantly worse WHODAS score or death at 1 year after surgery, (2) increased care needs or death at 6 months after surgery and (3) increased care needs or death at 1 year after surgery. We will use multivariable logistic regression models to determine the association of preoperative characteristics and surgery type with outcomes, joint modelling to characterise longitudinal time trends in WHODAS scores over 12 months after surgery, and longitudinal latent class mixture models to identify clusters following similar trajectories of disability. Ethics and dissemination: The FIT After Surgery study has received research ethics board approval at all sites. Recruitment began in December 2019 but was placed on hold in March 2020 because of the COVID-19 pandemic. Recruitment was gradually restarted in October 2020, with 1-year follow-up expected to finish in 2023. Publication of the primary results is anticipated to occur in 2024.